Assessment Smart Mobility of Citizen\'s View (Case Study:Shiraz City) - elahe kavoosi; Jamal Mohammadi (تحقیقات کاربردی علوم جغرافیایی)
The ‘Smart mobility’ has become an increasingly prevalent discussion topic in the past few years, not just in academic literature but also in cities’ policy and strategy. However,in many cities of the world and in our country, Iran has been associated with problems such as lack of citizen participation and inequality (caused by inefficient urban management). The present study has attempted with an innovative perspective to evaluate the existing infrastructure of mobility indicators (including transport infrastructure, public transport, sustainable transport, ICT) and the social dimensions of these infrastructures including the extent of citizen participation in use. Of these infrastructures) in eleven districts of Shiraz.The research method is descriptive-analytical and based on documentary and origin studies. Data gathering was field study by using a questionnaire. The 5-degree Likert spectrum technique was used to measure the value of indicators of the Smart Mobility. The results show that average smart mobility was higher in regions 1 and 6 than in other regions. the average smart mobility indicators are in 11 and 9 the lowest in other regions. The Urban Smart Mobility variable does not have an appropriate position in Shiraz, and this has not only affected its development process in recent decades, but also poses many challenges for its future development. Accordingly, urban planners should Consider the citizen participation and efficient urban management.